7C.07: ASSOCIATION OF SERUM FREE FATTY ACID LEVEL WITH REDUCED REFLECTION PRESSURE WAVE MAGNITUDE AND CENTRAL BLOOD PRESSURE. (June 2015) - Tabara, Y.; Takahashi, Y.; Kawaguchi, T.; Setoh, K.; Terao, C.; Yamada, R.; Kosugi, S.; Sekine, A.; Nakayama, T.; Matsuda, F.
Abstract : Objective: Central blood pressure (BP) has been suggested to be a better predictor of cardiovascular disease risk than brachial BP. Arterial stiffness increases central BP by early returning of the reflection pressure wave from peripheral arteries. Curiously, type 2 diabetes and insulin resistance have been favorably associated with central hemodynamics. Major initiators of insulin resistance—such as serum free fatty acid (FFA)—are thus suspected of potentially being involved in central hemodynamics. To confirm that insulin signaling is an important modulator of central hemodynamics, we investigated this hypothesis in a large-scale general population. Design and method: Brachial BP and radial arterial waveform were measured simultaneously in 9, 393 middle-aged to elderly individuals. The augmentation index (AIx) was calculated from the radial waveform as the ratio of the height of the late systolic peak to that of the first peak. Central systolic BP was defined as the absolute pressure of the late systolic peak of the waveform. Differences in central and brachial pulse pressure (PP) were considered to represent PP amplification. Results: PP amplification differed significantly among serum FFA level quartiles (Q1, 7.8 ± 5.3; Q2, 8.6 ± 5.0; Q3, 9.3 ± 5.7; Q4, 10.3 ± 6.1 mmHg, P < 0.001). As type 2 diabetes was also positively associated with PP amplification (diabetes, 10.5 ± 6.2; control 8.9 ± 5.6 mmHg, P < 0.001), the maximum difference reached 4.9 mmHg in combination analysis of FFA quartile and diabetes status. In contrast, AIx exhibited an inverse association with FFA quartile (Q1, 83.8 ± 12.8; Q2, 82.2 ± 12.9; Q3, 81.1 ± 13.3; Q4, 79.3 ± 13.4 %, P < 0.001). Multivariate analysis adjusted for major covariates indicated that higher serum FFA was an independent determinant for higher PP amplification (β = 0.145, P < 0.001) and lower AIx (β = −0.122, P < 0.001) and central systolic BP (β = −0.044, P < 0.001), while the association between FFA and PP amplification significantly decreased (β = 0.022, P < 0.001) after further adjustment for AIx. Conclusions: Serum FFA is an overlooked factor favorably influencing central hemodynamics. A low-magnitude reflection pressure wave might be involved in this paradoxical relationship.